Effects of various winter chilling regimes on flowering quality indicators of Greek olive cultivars - G. KOUBOURIS; I. LIMPERAKI; M. DARIOTI; C. SERGENTANI (Biologia Plantarum, 2019)
Aims of the present two-year study were to evaluate the feasibility and identify potential drawbacks of the greenhouse/outdoors parallel plant growth methods for investigation of the effects of various winter chilling regimes on flowering quality indicators of four Greek olive cultivars, namely Mastoidis, Amfissis, and Lefkolia Serron (originating from mountainous and colder areas) compared to cv. Koroneiki (grown mainly in plain warm areas). Groups of potted olive plants were either grown outdoors under ambient temperature or transferred into a greenhouse for one, two, or three months during winter in Crete, Greece. During the first year, chilling accumulation deficit caused a marked decrease in the number of inflorescences per plant in all four olive cultivars. In the second year, chilling accumulation deficit had a negative effect on the number of inflorescences per plant in 'Mastoidis' at 3-month greenhouse treatment but not at all in 'Koroneiki'. Chilling deficit caused an overall decrease in the number of flowers per inflorescence in both 'Koroneiki' and 'Mastoidis' as well as in the percentage of morphologically perfect flowers. The width and length of inflorescences were not affected by chilling deficit in both the cultivars. In vitro pollen germination was reduced in all greenhouse treatments in 'Koroneiki'; however, this effect was significant only after 3 month, whereas no effect was observed in 'Mastoidis'. The results of the present study may contribute to understanding olive flowering biology and selecting appropriate cultivars for new plantations according to historical meteorological data and predicted climate change scenarios.